The Generalised Settlement Area: mapping the Earth surface in the vicinity of built-up areas. Issue 1 (2nd January 2020) - Florczyk, A. J.; Melchiorri, M.; Zeidler, J.; Corbane, C.; Schiavina, M.; Freire, S.; Sabo, F.; Politis, P.; Esch, T.; Pesaresi, M.
ABSTRACT: Geo-information on settlements from Earth Observation offers a base for objective and scalable monitoring of the evolution of cities and settlements, including their location, extent and other attributes. In this work, we deploy the best available global knowledge on the presence of human settlements and built-up structures derived from Earth Observation to advance the understanding of the human presence on Earth. We start from a concept of Generalised Settlement Area to identify the Earth surface within which any built-up structure is present. We further characterise the resulted map by using an agreement map among the state of the art of remote sensing products mapping built-up areas or other strictly related semantic abstractions as urban areas or artificial surfaces . The agreement map is formed by a grid of 1 km 2, where each cell is classified according to the number of EO-derived products reporting any positive occurrence of the abstractions related to the presence of built-up structures. The paper describes the characteristics of the Generalised Settlement Area, the differences in the agreement map across geographic regions of the world, and outlines the implications for potential users of the EO-derived products used in this study.